Danish job advertisements: Increasing in complexity - Walters, Nina; Fage-Butler, Antoinette (Communication & Language at Work, 2014)
Although job advertisements have developed to incorporate an important array of functions, they are not well understood and there has been little documentation of evolution in the genre (Rafaeli & Oliver; 1998, 342). The purpose of this article is to address this gap by analysing changes in the genre over time, in this way revealing the background for current practice. Examples of Danish job advertisements for communication positions from 1961, 1991 and 2011 are analysed using Critical Discourse Analysis, and a rich format for job advertisements is developed on the basis of the findings of the analysis and existing theory. The results are likely to be of interest to producers of job advertisements who want a broader knowledge of how this genre with its increasingly complex functionality has evolved and for whom genre features of contemporary job advertising practice is relevant.